Development of syntactic comprehension and production in Friulian-Italian bilingual children - FRANZ, LUCIA; TAVANO, ALESSANDRO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2004)
In this paper we studied syntactic comprehension and production in 7 Friulian- Italian bilingual children aged 6 to 7 years. We aimed at: 1) assessing receptive and productive syntactic abilities in these age groups; 2) verifying whether in producing an elicited story children rely only on syntactic structures they perfectly understand or venture syntactic structures they master less than perfectly. Results show that first graders have similar receptive syntactic abilities in Italian and Friulian, while second graders show a great improvement in Italian but not in Friulian. This is attributed to the metalinguistic awareness of Italian they acquire at school. Furthermore, in the narrative task children seem to use only syntactic structures they master completely.